عرب جاہلیت کے بنیادی خط وخال؛ ایک تجزیاتی مطالعہ: Basic features of Arab Jāhilīya; an analytical study - Ali Chishti, Advocate Sajid; Khalid, Rimsha (Al-Amīr Research Journal for Islamic Studies, 2024)
The notion that the Arabs were an illiterate and uncivilized people has been fabricated. In fact, before the advent of Islam, several kingdoms, such as the Kingdom of Yemen, the Kingdom of Kindah, and the Kingdom of Ghassan, had established their own civilizations and cultures in different eras. The main reason for this false perception is the misinterpretation of the meaning and significance of "ignorance". In other words, the lack of literacy in Arab society was attributed to ignorance, and hence they were considered to be ignorant, even though they were a people with political, social, and economic awareness. In the view of the Arabs themselves, the well-known meaning of "ignorance" was taken as the opposite of "wisdom", and after the advent of Islam, this term was used to differentiate between Islamic and non-Islamic societies. In reality, "ignorance" refers to a particular mindset and behavior pattern on the basis of which a person assumes a personality that is in contrast to the personality described in the teachings of revelation, and as a result, he is seen to be a victim of excitement and lawlessness at the individual and social levels. Key Words: Arab, Nation, Jāhilīy(y)a, Khilāf al ilm, ḥilm, Civilization.